Penerapan Kriteria Sistem Jaminan Halal HAS 23000 Pada PT. Chiayo Sehat Indonesia - Sri Ayu Sri Ayu Parwati (POLITEKNIK PIKSI GANESHA, 2021)
Indonesia is one of the countries with the largest number of Muslims in the world. As a country with a Muslim majority population, the Muslim community needs an institution that becomes a reference or reference regarding issues regarding the laws of Islamic law. The Muslim community must guarantee this with regulations made through the Halal Assurance System. PT. Chiayo Sehat Indonesia is one of the businesses that provides halal-certified healthy food in Bandung. The importance of halal certification or halal label obtained makes PT. Chiayo has an obligation to implement a Halal Assurance System. The method used to analyze food halalness in this business is the Halal Assurance System (HAS) 23000. The purpose of this study is to determine the procedure for obtaining the MUI halal certificate and the application of the criteria for the HAS 23000 halal guarantee letter at PT. Chiayo Healthy Indonesia. This research begins by observing the field conditions of PT. Chiayo Healthy Indonesia. In collecting data used are interviews and documents. After knowing the field conditions, a halal assurance system is prepared and implemented. The halal assurance system has eleven criteria. These criteria are used as a reference for the issuance of halal certificates and production implementation guidelines. Observations on eleven aspects of halalness in HAS 23000, namely (1) Halal Policy, (2) Halal Management Team, (3) Training, (4) Materials, (5) Products, (6) Product Facilities, (7) Written Procedures for Critical Activities , (8) Traceability, (9) Handling of Products that do not Meet the Criteria, (10) Internal Audit, (11) and Management Review. Keywords: Halal Assurance System, Healthy Food, Halal